2016
DOI: 10.1371/journal.pone.0167654
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Potential ART Adherence Monitoring Interventions in Sub-Saharan Africa

Abstract: BackgroundInterventions based around objective measurement of adherence to antiretroviral drugs for HIV have potential to improve adherence and to enable differentiation of care such that clinical visits are reduced in those with high adherence. It would be useful to understand the approximate upper limit of cost that could be considered for such interventions of a given effectiveness in order to be cost effective. Such information can guide whether to implement an intervention in the light of a trial showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…Pill counting can be implemented at any clinic, and pharmacy refill data is already widely available and an immediately implementable option, particularly in resource-poor settings. Consideration should also be given to the use of electronic measures as adherence monitoring strategies as costs reduce [40]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pill counting can be implemented at any clinic, and pharmacy refill data is already widely available and an immediately implementable option, particularly in resource-poor settings. Consideration should also be given to the use of electronic measures as adherence monitoring strategies as costs reduce [40]. …”
Section: Resultsmentioning
confidence: 99%
“…However, recent data shows EAMD can reduce costs associated with HIV-RNA monitoring and real-time devices can detect early virologic rebound before established failure [3, 38, 39]. With the availability of newer, more affordable real-time technologies, electronic strategies should be reconsidered [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Over time, the ability to focus resources on patients at high risk of virologic failure, as well as the probable decline in technology cost, may make these interventions cost-neutral or cost-saving [112]. Importantly, recent modelling found that EDM would be cost-effective with or without the availability of viral load testing at <US$50 [113]. Additionally, ICT-enhanced solutions have generally been acceptable to PLWH [114], which will facilitate scale up, although privacy (e.g.…”
Section: Electronic Pharmacy Refill Tracking Systemsmentioning
confidence: 99%
“…Finally, cost is an obvious concern when considering technology for clinical care. Cost-effectiveness is beyond the scope of this analysis; however, a cost-effectiveness analysis of potential ART adherence monitoring interventions in sub-Saharan Africa found that an adherence monitoring-based intervention could cost up to $50 per person-year on ART while remaining cost-effective, mainly driven by savings through effective differentiation of care [8]. Current lower cost versions of real-time adherence monitoring devices consistent with that threshold [40] are now available and are being tested for use in routine care (NCT03825952).…”
Section: Discussionmentioning
confidence: 99%